O USO DA MÚSICA COMO UMA PRÁTICA DE SAÚDE NAS SESSÕES DE HEMODIÁLISE: RELATO DE EXPERIÊNCIA1 - Poli, Ane G.; Althaus, Jucieli C.; Hartmann, Simoni; Terra, Laíza F.; Ubessi, Liamara D.; Taborda, Douglas d. S.; Poli, Gilmar (Salão do Conhecimento, 2013)
Resumo